Contesting "Authenticity" in Authentic Leadership through a Mad Studies Lens. (September 2021) - Procknow, Greg; Rocco, Tonette S.
A Mad Studies/social model of mental distress lens was used to critique authentic leadership. We deconstructed the dilemma of authenticity and leadership by exploring how authentic leadership (dis)allows the inclusion of people with mental illness. We found that their minds are treated as disruptive and rarely ever read as authentic. For followers to view "mentally ill" leaders as authentic requires candidness, disability disclosure, and emulating norms typical to their ingroup membership. We conclude this paper by challenging HRD to rethink its stance on disruptive leadership as symptomatic of mental illness. Employees with mental health marginality can develop an authentic identity in the workplace through authenticity building experiences such as connecting mad leaders to peer-support training, offering specialized leadership development, and co-producing a mental health awareness curriculum that challenges unhealthy workplace discourses that stigmatize mad leaders and workers.